Avaliação do padrão Simple Knowledge Organization System (SKOS) para a representação de vocabulários controlados - Sousa, Janailton Lopes (Universidade Federal de São Carlos, 2019)
Knowledge Organization System (KOS) are information resources representation tools used in Information Science, the KOS background includes the study of the concepts and use of digital technological instruments. The Simple Knowledge Organization System (SKOS) represents this junction between the KOS theoretical foundation and its conceptual frameworks, with the use of digital representation tools, favoring the representation of a traditional KOS in digital environments. However, the increase in controlled vocabulary publications, available in digital environments, points to the need to identify new evaluation procedures for these instruments. In this sense, the general objective of this research is to identify evaluation parameters of the SKOS standard, for the representation of controlled vocabularies. This research is theoretical and methodological, with a qualitative approach and exploratory character, which aims to examine the themes of representation, organization, semantic technologies and vocabulary availability in digital environments. As a result of this research, evaluation parameters are presented that can be applied in SKOS-coded vocabularies, thus serving as a reference source that can assist research in this theme. It is concluded that the difficulty of evaluating controlled vocabularies is still present, in this sense, the use of parameters that can help this process contributes to the advancement of discussions that include this theme in the field of study of the Knowledge Organization.
Evaluation of the Simple Knowledge Organization System (SKOS) Standard for controlled vocabulary representation
Keywords: Knowledge Organization System; Vocabulários controlados; Tesauros; Simple Knowledge Organization System; Avaliação de vocabulários controlados; SKOS; Vocabularies controlled; Thesauri; Evaluation vocabularies controlled; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA